Control of interpenetration of copper-based MOFs on supported surfaces by electrochemical synthesis. Issue 22 (15th January 2016) - Sachdeva, Sumit; Pustovarenko, Alexey; Sudhölter, Ernst J. R.; Kapteijn, Freek; de Smet, Louis C. P. M.; Gascon, Jorge
Abstract : A study of a copper-based metal–organic framework (MOF) synthesized by an electrochemical route is presented. Abstract : A study of a copper-based metal–organic framework (MOF) synthesized by an electrochemical route is presented. Morphological and adsorption properties of the MOF synthesized as bulk powder and on supported copper surfaces were investigated. Differences in these properties and structural refinement studies indicate that when 4, 4′, 4′′- s -triazine-2, 4, 6-triyl-tribenzoic acid (H3 TATB) is used as linkeri nterpenetration can be prevented when the structure is grown on a surface.